¿Se ha dado cumplimiento al Decreto 1122 de 1998, para la implementación de la Cátedra de Estudios Afrocolombianos consagrada en la Ley 70 de 1993 en los Colegios Públicos del Municipio de Puerto Tejada Cauca en el periodo comprendido entre el año 2013 y el 2019? (2021)
In the following paper, we analyzed compliance of the decree 1122, from 1998. This covers the implementation of the chairperson of Afro-Colombian studies relating to law 70 from 1993 in the public schools of the town of Puerto Tejada Cauca during the period of 2013 to 2019. Through the conceptual review and regulations of the chairperson as a tool that would promote the rights of Inclusion and cultural identification of the black population. Multiple interviews were undertaking with the educated of the institution in their relevant fields of researching with the entities involved in the implementation of the chair; The information provided was collected, interpreted and analyzed to determine the methodologies, barriers and recommendations presented to the institution of the town.